Phosphorylation of Cardiac Myosin-Binding Protein-C Is a Critical Mediator of Diastolic Function. (May 2015) - Rosas, Paola C.; Liu, Yang; Abdalla, Mohamed I.; Thomas, Candice M.; Kidwell, David T.; Dusio, Giuseppina F.; Mukhopadhyay, Dhriti; Kumar, Rajesh; Baker, Kenneth M.; Mitchell, Brett M.; Powers, Patricia A.; Fitzsimons, Daniel P.; et al.
<x xml:space="preserve">Abstract</x> Background— Heart failure (HF) with preserved ejection fraction (HFpEF) accounts for ≈50% of all cases of HF and currently has no effective treatment. Diastolic dysfunction underlies HFpEF; therefore, elucidation of the mechanisms that mediate relaxation can provide new potential targets for treatment. Cardiac myosin-binding protein-C (cMyBP-C) is a thick filament protein that modulates cross-bridge cycling rates via alterations in its phosphorylation status. Thus, we hypothesize that phosphorylated cMyBP-C accelerates the rate of cross-bridge detachment, thereby enhancing relaxation to mediate diastolic function. Methods and Results— We compared mouse models expressing phosphorylation-deficient cMyBP-C(S273A/S282A/S302A)–cMyBP-C(t3SA), phosphomimetic cMyBP-C(S273D/S282D/S302D)–cMyBP-C(t3SD), and wild-type-control cMyBP-C(tWT) to elucidate the functional effects of cMyBP-C phosphorylation. Decreased voluntary running distances, increased lung/body weight ratios, and increased brain natriuretic peptide levels in cMyBP-C(t3SA) mice demonstrate that phosphorylation deficiency is associated with signs of HF. Echocardiography (ejection fraction and myocardial relaxation velocity) and pressure/volume measurements (−dP/dtmin, pressure decay time constant τ-Glantz, and passive filling stiffness) show that cMyBP-C phosphorylation enhances myocardial relaxation in cMyBP-C(t3SD) mice, whereas deficient cMyBP-C phosphorylation causes diastolic dysfunction with HFpEF in cMyBP-C(t3SA) mice. Simultaneous force and [Ca2+]i measurements on intact papillary muscles show that enhancement of relaxation in cMyBP-C(t3SD) mice and impairment of relaxation in cMyBP-C(t3SA) mice are not because of altered [Ca2+]i handling, implicating that altered cross-bridge detachment rates mediate these changes in relaxation rates. Conclusions— cMyBP-C phosphorylation enhances relaxation, whereas deficient phosphorylation causes diastolic dysfunction and phenotypes resembling HFpEF. Thus, cMyBP-C is a potential target for treatment of HFpEF.